INTERAKTIVNO UČENJE U FIZIČKOM VASPITANJU - Grujo Bjeković; Proko Dragosavljević; Vesna Bratovčić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Interactive learning at PT presents interpersonal relationship between teacher and students, students among themselves, as well as students and parents and broader community. This modern method of learning creates good emotional environment in the class, motivates the students, develops cooperation among them and increases the level of responsibility in the students. A teacher who undergoes the training of how to use the methods, forms and techniques of interactive learning will advance and improve his/her previous experience. It is of great importance to find, as much theoretical as, practical answers to the question why and how to establish interactive learning at PT. It starts, mainly, with forming pairs, small groups/classes, and then follows with different methods of interaction in actual behavior, methods and workshops applicable to the PT education.